PENGARUH PEMBERIAN EKSTRAK BUAH DELIMA MERAH (Punica granatum) TERHADAP KADAR F2-IsoPs PADA KULTUR HUVECs YANG DIPAPAR PLASMA PREEKLAMPSIA - Januarsih; Megawati; Fitria Jannatul Laili (Rena Cipta Mandiri, 2025)
Preeclampsia is a leading cause of maternal mortality associated with oxidative stress. Elevated F2-Isoprostanes (F2-IsoPs) serve as biomarkers of lipid peroxidation. This study aimed to determine the effect of red pomegranate (Punica granatum) extract on F2-IsoPs levels in HUVEC cultures exposed to preeclamptic plasma. A true experimental post-test only control group design was used with five groups (n=5 each): K– (normal plasma), K+ (preeclamptic plasma), P1 (14 ppm), P2 (28 ppm), and P3 (56 ppm). F2-IsoPs levels were measured using ELISA and analyzed with one-way ANOVA and LSD post hoc tests. Results showed significantly higher F2-IsoPs levels in K+ compared to K– (p<0.05). Red pomegranate extract reduced F2-IsoPs levels in a dose-dependent manner, with the greatest reduction at 56 ppm. Conclusion: Punica granatum extract exhibits antioxidant potential against oxidative stress in preeclampsia.